18 years of face transplantation: Adverse outcomes and challenges - Longo, Benedetto; Pomahac, Bohdan; Giacalone, Martina; Cardillo, Massimo; Cervelli, Valerio (Journal of plastic, reconstructive & aesthetic surgery, 2023)
BACKGROUND: Since the first procedure performed in 2005, face transplantation has been debated as viable approach for the treatment of severe craniofacial defects. Despite the benefits provided, the experience in face allotransplantation has brought to light a significant risk of complications, including allograft removal or loss, and mortality. The present study is intended to provide an updated review on complications and major challenges witnessed over 18 years of experience in the field. METHODS: A systematic review of PubMed, MEDLINE, Cochrane, Google, and Google Scholar databases on face transplantation was conducted according to PRISMA guidelines up to April 2023. Articles providing details on cases of face allograft loss, removal, and patient death were included. Online articles and media reports were assessed to include information not disclosed in peer-reviewed literature. Face transplant centers were contacted to have updated follow-up information on single-face transplant cases. RESULTS: The search yielded 1006 reports, of which 28 were included. On a total of 48 procedures performed in 46 patients, adverse outcomes were gleaned in 14 cases (29%), including seven allograft losses (14.6%), and the death of ten patients (21.7%). Chronic rejection was the leading cause of allograft loss, with a median time from transplant to irreversible rejection of 90 months (IQR 88.5-102). The main causes of death were infectious complications, followed by malignancies, non-compliance to immunosuppression, and suicide. The median time to death was 48.5 months (IQR 19-122). CONCLUSIONS: To the best of our knowledge, this is the first study providing a comprehensive review of adverse outcomes in face transplantation. Considering the high rate of major complications, the heterogeneity of cases and single-center approaches, and the absence of published standards of care, the development of a consensus by face transplant teams holds the key to the field's advancement.
Keywords: rejekce štěpu; imunologická tolerance; lidé; transplantace obličeje; Immunosuppression Therapy; Graft Rejection; imunosupresivní léčba; Humans; Immune Tolerance; Facial Transplantation